The Pentagon's Brain : An Uncensored History of DARPA, America's Top Secret Military Research Agency - Jacobsen, Annie (New York Little, Brown and Company, 2015)
The definitive history of DARPA, the Defense Advanced Research Project Agency, from the author of the New York Times bestseller Area 51
Include Bibliography and Index
Keywords: a